Bone imaging in hypoparathyroidism. Issue 2 (February 2017) - Silva, B.; Rubin, M.; Cusano, N.; Bilezikian, J.
Abstract Hypoparathyroidism (HypoPT) is an uncommon endocrine disorder characterized by chronic deficiency or absence of parathyroid hormone (PTH), which leads to a profound reduction in bone remodeling. Subjects with HypoPT typically have bone mineral densities (BMDs) by dual-energy X-ray absorptiometry (DXA) above average at all skeletal sites, with greatest scores observed at the lumbar spine. Trabecular bone score (TBS), an indirect measure of bone microarchitecture, also appears to be normal in HypoPT. By peripheral quantitative computed tomography (pQCT) of the radius, volumetric BMD at cancellous and cortical compartments, as well as cortical area and thickness, are greater in hypoparathyroid subjects than in controls. The use of high-resolution pQCT (HRpQCT) confirmed the increase in cortical volumetric BMD but demonstrated reduced cortical thickness, associated with lower cortical porosity in HypoPT. Trabeculae tend to be more numerous but thinner in hypoparathyroid subjects. It is not clear whether these structural and the dynamic skeletal abnormalities in HypoPT affect bone strength or fracture risk. Treatment of HypoPT with PTH leads to improvement in bone remodeling rate, variable changes in bone density, and a transient increase in estimated bone strength. The effect of PTH therapy on fracture risk remains unknown. This article reviews skeletal involvement and the effect of PTH treatment in patients with HypoPT, as assessed by DXA, TBS, QCT, and HRpQCT. Data on bone strength and fracture risk in HypoPT are also reviewed here.